2013
DOI: 10.1103/physrevb.87.241405
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the detection and braiding of Majorana fermions in a quantum spin Hall insulator

Abstract: We show how a quantum dot with a ballistic single-channel point contact to a superconductor can be created by means of a gate electrode at the edge of a quantum spin Hall insulator (such as an InAs/GaSb quantum well). A weak perpendicular magnetic field traps a Majorana zero mode, so that it can be observed in the gate-voltageaveraged differential conductance dI/dV as a 4e2 /h zero-bias peak above a ( 2 3 π 2 − 4)e 2 /h background. The one-dimensional edge does not permit the braiding of pairs of Majorana ferm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 47 publications
4
80
0
Order By: Relevance
“…Again, the maximal polarization is attained when the dot level is above or below the Fermi energy on the scale of the hybridization width because Eq. (23) shows that the spin current is proportional to t , which is a function with an energy dependence governed by in the Breit-Wigner approximation. Furthermore, our results show that the polarization decreases when the background temperature T increases since large temperatures tend to smear out the energy dependence of the scattering matrix, an essential ingredient of our spin-filter effect.…”
Section: A Voltage-driven Transport: Isothermal Casementioning
confidence: 99%
See 1 more Smart Citation
“…Again, the maximal polarization is attained when the dot level is above or below the Fermi energy on the scale of the hybridization width because Eq. (23) shows that the spin current is proportional to t , which is a function with an energy dependence governed by in the Breit-Wigner approximation. Furthermore, our results show that the polarization decreases when the background temperature T increases since large temperatures tend to smear out the energy dependence of the scattering matrix, an essential ingredient of our spin-filter effect.…”
Section: A Voltage-driven Transport: Isothermal Casementioning
confidence: 99%
“…A feasible possibility is the application of local potentials to form quantum antidots. More generally, the presence of constrictions in two-dimensional topological insulators have been proposed to give rise to coherent oscillations [18], transformations between ordinary and topological regimes [19], peaks of noise correlations [20], metal-to-insulator quantum phase transitions [21], nonequilibrium fluctuation relations [22], braiding of Majorana fermions [23], competition between Fabry-Pérot and Mach-Zehnder processes [24], control of edge magnetization [25], and detection of Kondo clouds [26]. Interestingly, König et al have experimentally demonstrated [27] the local manipulation of helical states with back-gate electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent proposed scheme to realize Majorana fermions by using the spin-orbit interaction and Zeeman field [10][11][12][13][14] was eventually applied to a one-dimensional nanowire with proximity induced swave pairing [15,16], which can be fabricated by the present experimental technique [17][18][19][20][21][22]. Furthermore, varieties of proposals exist in order to improve the experimental accessibility and controllability of Majorana modes [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…However, it can be effectively realized in spinful systems by a combination of spin-orbit coupling and explicitly lifting the Kramer's degeneracy of the electrons (e.g., by Zeeman spin splitting through an applied magnetic field). This idea has lead to a number of proposals for realizing topological superconductor in various hybrid structures with conventional s-wave superconductors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . There are, however, significant differences between a spinless p-wave superconductor and a spin-split s-wave superconductor with spin-orbit coupling although they both can have localized MZMs at the ends.…”
Section: Introductionmentioning
confidence: 99%